How can Archaeological Scientist Integrate the Typological and Stylistic Characteristics with Scientific Results: A Case Study on Bronze Spearheads Unearthed from the Shuangyuan Village, Chengdu City, Southwest China - Wang, Xiaoting; Yang, Yingdong; Wang, Tianyou; Chen, Dian; Luo, Wugan (Current Analytical Chemistry, 2021)
Background: Bronze spears are weapons with unique regional characteristics of the Shu culture, Southwest China in the Bronze Age, which reflect the bronze manufacturing tradition and the utilization of mineral resources of ancestors. Previous studies mainly focused on the classification, the alloy composition, or the production of bronze spearheads of the Shu culture. The purpose of this paper was to make a comprehensive discussion on the Shu culture from the aspects of the relationship between typology and scientific characteristics, the differences in metal raw material selection with the Ba culture, and the contact with the culture in the Central Plains. Methods: In this study, typology, portable X-ray fluorescence spectrometry (pXRF) and multicollector inductively coupled plasma mass spectrometry (MC-ICP-MS) were used to analyze thirteen bronze spearheads unearthed from Shuangyuan site, an Eastern Zhou cemetery in Chengdu City, Sichuan Province, Southwest China. Results: The results show that the spearheads can be classified into three types in typology. All samples are tin-lead ternary bronzes, and the lead isotope data indicate the lead ore. Most spearheads show ordinary lead, and only one spearhead has highly radiogenic lead. Conclusion: The typical Shu-style bronze spearheads have distinct shapes but similar ore materials. Meanwhile, people of the Ba culture and the Shu culture used different metal sources to make bronze spearheads. In addition, a very special bronze spearhead suggests that ancestors of the Shu culture in the Eastern Zhou Dynasty imitated the late Shang culture in the Central Plains.
Keywords: the eastern zhou dynasty